Evaluating the resilience level among nursing students in usm and its association to psychological parameters - Vesupathy, Logeswarry K (2024)
The level of resilience among nurses and nursing students is known to be high globally nd also in our country, Malaysia. Resilience is associated with many psychosocial and psychological factors especially stress, depression and anxiety among nurses and nursing students. The study aimed to evaluate the resilience level among nursing students in USM and its association to psychological parameters. A total of 240 nursing students at the School of Health Sciences USM were invited to participate in the study. The students were from year one to year four selected using purposive sampling . An online Google Form questionnaire consisting of demographic data, Connor-Davidson Resiliency Scale 25 (CD-RISC 25)and the General Health Questionnaire (GHQ-28) was distributed using WhatsApp application. Demographic data included gender, age, years of study and educational level. The outcome was in the form of level of resilience in which was categorised into significant and non-significant resilience level based on the CD-RISC 25 score. Each domain of resilience was analysed using appropriate statistical analysis. Gender and educational level were analysed using an independent t-test. Next, years of study and age were analysed using One way ANOVA test. A total of 186 USM nursing students responded. The response rate was 77.5%. The distribution of nursing students responded was according to the current proportion by gender, age, educational level and year of study. The highest mean among five domains of resilience scale was management of negative emotions or stress with Mean:3.621(SD:0.68). There was a negative correlation between gender and years of study in domains of resilience scale and it was statistically significant (P< 0.001). Resilience level was significantly associated level of education and age. In addition, association of level of resilience and psychological parameters was analysed using multiple linear regression test. There were association of domains of resilience scale associated with parameters of psychological score which are somatic symptoms and anxiety and insomnia. As a conclusion, there was high resilience among nursing students in USM and the level of resilience was associated with psychological parameters. Hence, measures need to be taken to enhance resilience among nursing students to overcome psychological distress academically and clinically. Resilience should be possessed by nursing students to overcome psychological challenges.